New species and new records of Ampithoidae (Peracarida: Amphipoda) from Australian Waters - Hughes, Lauren E.; Peart, Rachael A. (Zootaxa, 2013)
Forty-eight species from the algal dwelling family Ampithoidae are recorded from five genera Ampithoe, Cymadusa, Paragrubia, Peramphithoe, and Plumithoe. New distribution records are provided for 18 species including five new records from Australian waters and an additional 18 new species are described. Twenty-two Ampithoe, 23 Cymadusa, six Paragrubia, two Peramphithoe, and one Plumithoe species are now known from Australian waters. The generic concepts of both Cymadusa and Paragrubia are revised to accommodate the new species diversity within the Ampithoidae. The new species are: Ampithoe mantissa; A. prolata; Cymadusa botulus; C. drummondae; C. euclidius; C. hadros; C. hallex; C. hentyana; C. jubata; C. lumanus; C. platys; C. priscileo; Paragrubia apoorei; P. cassini; P. dongara; P. dwyeri; P. springthorpei and Peramphithoe bungareei.